2008
DOI: 10.1179/174313208x327955
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomical evidences for potential of mesenchymal stem cells in amelioration of striatal degeneration

Abstract: Huntington's disease is an inherited neurodegenerative disorder, characterized by loss of spiny neurons in the striatum and cortex, which usually happens in the third or fourth decades of life. In advanced form of the disease, progressive striatum atrophy happens and medium spiny neurons, which occupy more than 80% of the striatum, become atrophic. Gradually, the atrophy expands to the neocortex and other regions of the brain. To our knowledge, there is no effective therapeutic strategy for diminishing the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Transplanting autologous bone marrow stem cells in the damaged striatum of a rat HD model significantly reduced working memory deficits [59]. Meanwhile, the volume of the lateral ventricle returned to a significantly smaller size, approaching the normal contralateral ventricle after MSCs implantation [60]. Mesenchymal stem cell transplantation may help stabilize the striatal environment by producing anti-inflammatory cytokines and neurotrophic factors.…”
Section: Mscs For the Treatment Of Neurodegenerative Diseasementioning
confidence: 98%
“…Transplanting autologous bone marrow stem cells in the damaged striatum of a rat HD model significantly reduced working memory deficits [59]. Meanwhile, the volume of the lateral ventricle returned to a significantly smaller size, approaching the normal contralateral ventricle after MSCs implantation [60]. Mesenchymal stem cell transplantation may help stabilize the striatal environment by producing anti-inflammatory cytokines and neurotrophic factors.…”
Section: Mscs For the Treatment Of Neurodegenerative Diseasementioning
confidence: 98%
“…Bantubungi et al [72] found that the lesioned environment of the striatum favored the proliferation and intralesional distribution of MSC. Several groups have shown that striatal atrophy in models of HD is accompanied by the subsequent enlargement of lateral ventricles [73, 74]. The reduction in volume of the lateral ventricle can thus be a good indicator of repair in HD correction studies.…”
Section: Huntington’s Diseasementioning
confidence: 99%
“…The reduction in volume of the lateral ventricle can thus be a good indicator of repair in HD correction studies. Amin et al [73] demonstrated that after MSC implantation into the striata of rats with a unilateral damage model of HD, striatal atrophies were significantly reduced. Consequently, the volume of the lateral ventricle returned to a significantly smaller size, approaching the normal contralateral ventricle.…”
Section: Huntington’s Diseasementioning
confidence: 99%
“…More recently, transplantation of MSCs, either intracerebrally or intravenously, resulted in a decreased atrophy of lesioned rat striatum (Amin et al, 2008) and in some functional benefits (Edalatmanesh et al, 2009) even though only a fraction of cells (1 %) expressed neural phenotypes. Thus, it was suggested that MSCs, by producing growth factors, allowed surviving cells within the caudate nucleus to function more efficiently and to facilitate other compensatory responses (Dunbar et al, 2006).…”
Section: Adult Cell Therapymentioning
confidence: 99%